Representing the patient experience of heart failure through empathy, journey and stakeholder mapping - Leanna Woods; Jed Duff; Erin Roehrer; Kim Walker; Elizabeth Cummings (The Beryl Institute, 2019)
Heart failure is a long-term condition requiring those affected to manage numerous self-care related activities. People with heart failure report multiple challenges accommodating self-care activities in their every-day life. The aim of this study is to (1) understand the experience of people with heart failure and their caregivers in the local patient population, and (2) visually represent these experiences to inform the design of a mobile health intervention supporting self-care. Seven patients and four family caregivers were interviewed using an empathic approach. Data was collected using rapid design methods including an empathy map to uncover patient and caregiver perspectives and a journey map to document daily self-care activities. Content analysis resulted in a needs and insights summary, a journey map and stakeholder map. The needs and insights are summarised in five themes; controlling, trusting, concerned, symptom-laden and accepting. Negative experiences - restlessness, breathlessness and urination - occurred overnight as visualised in the journey map. Overwhelmingly the spouse and general practitioner were the personal and professional stakeholders involved in self-care activities. Understanding the experience of people with heart failure was the first step in the creation of a patient-centred mobile health intervention. Rapid design methods such as the three presented in this paper can give voice to the patient experience, their frustrations, challenges and existing support structures in a clear, visual format to aid empathic design.